1996
DOI: 10.1007/bf02814663
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of yeast ethanol tolerance by calcium and magnesium

Abstract: Ethanol-induced changes of CO2 production were compared in three strains of Saccharomyces cerevisiae. CaCl2 and MgCl2 exerted protective effects against the action of ethanol. Optimal concentrations ensuring maximum of CO2 production at 10% (V/V) of ethanol under non-growing conditions were 3 mmol/L Ca2+ and 2 mmol/L Mg2+. Yeast growth with and without ethanol addition was stimulated by Mg2+ more than by Ca2+ during fermentation, whereas ethanol production was more efficient when both Ca2+ and Mg2+ were added.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 12 publications
0
16
0
2
Order By: Relevance
“…A nutrient transfer from fibers to cell can cause the disruption of the fibrillar structure of chrysotile, as shown in Figure 2E. The importance of Mg for cellular reproduction and fermentative metabolism has been extensively reported in the literature (Walker and Maynard, 1997;Ciesarová et al, 1996), but Mg alone does not show the same effect as the brucite surface layer of chrysotile for the adhesion of cells . Also, Mg uptake by the cells should be much smaller than the quantities available in the chrysotile surface, or in the solution, since Mg is a metabolic co-factor.…”
Section: A B C D Ementioning
confidence: 76%
See 1 more Smart Citation
“…A nutrient transfer from fibers to cell can cause the disruption of the fibrillar structure of chrysotile, as shown in Figure 2E. The importance of Mg for cellular reproduction and fermentative metabolism has been extensively reported in the literature (Walker and Maynard, 1997;Ciesarová et al, 1996), but Mg alone does not show the same effect as the brucite surface layer of chrysotile for the adhesion of cells . Also, Mg uptake by the cells should be much smaller than the quantities available in the chrysotile surface, or in the solution, since Mg is a metabolic co-factor.…”
Section: A B C D Ementioning
confidence: 76%
“…It seems that the brucite layer is acting as an adhesive surface, probably through acid-base interactions with the glycoproteins of the cell wall (Kida et al, 1992;Mozes et al, 1987). Besides that, the entrapment can act as a protection for the cells against environmental stress (Ciesarová et al, 1996), once the Saccharomyces cerevisiae cells are still active for fermentation following one-year storage in the absence of nutrients. This protection can be a mechanical protection.…”
Section: A B C D Ementioning
confidence: 99%
“…The addition of inorganic salts such as Mg 2+ , which also act as an activator of some enzymes in yeast cells will promote the ethanol yield [8,16]. Thus, supplementation of fermentation media with magnesium has been shown to increase fermentation rate and ethanol productivity [8,14,17]. Liu et al [8] also reported that (NH 4 ) 2 SO 4 and MgSO 4 are the most important nutrient to improve the bioethanol yield from sugar by yeast fermentation.…”
Section: Influence Of Nutrient Addition To Bioethanol Yield and Sugarmentioning
confidence: 97%
“…2B shows the bioethanol concentration with MgSO 4 addition of 34.64 g/l and the bioethanol yield of 76.13% at 24 h. The yield of ethanol with addition of MgSO 4 was much higher (at least 20% higher) than those without additive. This may be attributed to the increase in ethanol tolerance of S. cerevisiae with Mg 2+ addition [14].…”
Section: Fermentation Profile With and Without Nutrient Additionmentioning
confidence: 99%
“…Calcium, being actively excluded from the yeast cell, acts mainly extracellularly for example, calcium is essential for amylase activity [25]. Metal ion deficiencies often occur in fermentation media, and studies on optimization of metal ions combinations are thus of great practical importance to improve bioethanol production [1,26].…”
Section: Introductionmentioning
confidence: 99%